Income Inequality and Tax Policy for South African Race Groups - Berg, Gregory D.; Kaempfer, William H. (The Review of Economics and Statistics, 2003)
This paper calculates elasticities of demand for race groups in South Africa, government-revenue-maximizing tax rates, and excess burdens associated with taxes. A change in tax policy can be the political engine of income redistribution with appropriate taxes and subsidies on different commodities. This paper compares both semiparametric and parametric estimators with the censored least absolute deviation and censored maximum likelihood in calculating demand equations and elasticities. It is found that cigarettes and milk are the two commodities that generate the most government revenues from whites per unit of government revenues from blacks.